1990
DOI: 10.2307/2328717
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Stock Returns in an Efficient Market

Abstract: An intertemporal general equilibrium model relates financial asset returns to movements in aggregate output. The model is a standard neoclassical growth model with serial correlation in aggregate output. Changes in aggregate output lead to attempts by agents to smooth consumption, which affects the required rate of return on financial assets. Since aggregate output is serially correlated and hence predictable, the theory suggests that stock returns can be predicted based on rational forecasts of output. The em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(111 citation statements)
references
References 4 publications
6
105
0
Order By: Relevance
“…Recent studies (e.g. Balvers, Cosimano, & McDonald, 1990;Breen, Glosten, & Jagannathan, 1990;Campbell, 1987;Campbell & Hamao, 1992;Cochrane, 1991;Fama & French, 1989;Ferson & Harvey, 1993;French, Schwert, & Stambaugh, 1987;Glosten, Jagannathan, & Runkle, 1993;Keim & Stambaugh, 1986;Pesaran & Timmerman, 1995) have shown that this conclusion holds across a variety of stock markets and time horizons despite its implication for market efficiency. 1 In a recent advancement Timmerman (1995, 2000) using a linear recursive modelling strategy examined the robustness of predictability of US and UK stock market returns by simulating the behaviour of investors who search in 'real time' for a model that can forecast stock returns.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent studies (e.g. Balvers, Cosimano, & McDonald, 1990;Breen, Glosten, & Jagannathan, 1990;Campbell, 1987;Campbell & Hamao, 1992;Cochrane, 1991;Fama & French, 1989;Ferson & Harvey, 1993;French, Schwert, & Stambaugh, 1987;Glosten, Jagannathan, & Runkle, 1993;Keim & Stambaugh, 1986;Pesaran & Timmerman, 1995) have shown that this conclusion holds across a variety of stock markets and time horizons despite its implication for market efficiency. 1 In a recent advancement Timmerman (1995, 2000) using a linear recursive modelling strategy examined the robustness of predictability of US and UK stock market returns by simulating the behaviour of investors who search in 'real time' for a model that can forecast stock returns.…”
Section: Introductionmentioning
confidence: 96%
“…While Balvers et al (1990) construct a general equilibrium model relating asset returns to macroeconomic fluctuations in a context that is consistent with efficient markets.…”
Section: Introductionmentioning
confidence: 99%
“…Lintner (1975), Famaand Schwert (1977), and Fama (1981 utilize economic variables such as the inflation rate. Balvers, Cosimano and McDonald (1990) and Schwert (1990) use industrial production. Campbell (1987), Hodrick (1992), and Ang and Bekaert (2007) employ short-term interest rates.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Moreover, as in Fama and French (1988a) and Balvers et al (1990), it is concluded that predictability is not necessary inconsistent with the concept of market efficiency. Fama (1991) examines the links between expected returns and macro-variables and acknowledges the existence of connection between expected returns and shocks to tastes or technology (changes of business conditions).…”
Section: Introductionmentioning
confidence: 97%